Revision of the spider genus Epiceraticelus (Araneae, Linyphiidae) with a description of a new species - Draney, Michael L.; Milne, Marc A.; Ulyshen, Michael; Madriz, Gabrielle (Zootaxa, 2019)
The type species of the genus, Epiceraticelus fluvialis Crosby & Bishop, 1931, is herein redescribed since the types are presumed lost. In addition, a new species, Epiceraticelus mandyae n. sp., from the Southeastern United States is described.